Simulating Grasping Behavior on an Imaging Interactive Surface - Wilson, Andy (ITS '09 Proceedings of the ACM International Conference on Interactive Tabletops and Surfaces, 2009)
We present techniques and algorithms to simulate grasping behavior on an imaging interactive surface (e.g., Microsoft Surface). In particular, we describe a contour model of touch contact shape, and show how these contours may be represented in a real-time physics simulation in a way that allows more realistic grasping behavior. For example, a virtual object may be moved by “squeezing” it with multiple contacts undergoing motion. The virtual object is caused to move by simulated contact and friction forces. Previous work uses many small rigid bodies (“particle proxies”) to approximate touch contact shape. This paper presents a variation of the particle proxy approach which allows grasping behavior. The advantages and disadvantages of this new approach are discussed.